Moving to Despair? Migration and Well-Being in Pakistan - Joyce J. Chen; Katrina Kosec; Valerie Mueller (Institute of Labor Economics (IZA), 2017)
Internal migration has the potential to substantially increase income, especially for the poor in developing countries, and yet migration rates remain low. We explore the role of psychic costs by evaluating the impacts of internal migration on a suite of well-being indicators using a unique, 22-year longitudinal study in rural Pakistan. We account for selection into migration using covariate matching. Migrants have roughly 35 to 40 percent higher consumption per adult equivalent, yet are 12 to 14 percentage points less likely to report feeling either happy or calm. Our results suggest that deteriorating physical health coupled with feelings of relative deprivation underlie the disparity between economic and mental well-being. Thus, despite substantial monetary gains from migration, people may be happier and less mentally distressed remaining at home. If traditional market mechanisms cannot reduce psychic costs, it may be more constructive to address regional inequality by shifting production – rather than workers – across space.
Keywords: J61; O15; I31; 330; internal migration; psychic costs; well-being; Pakistan